2020
DOI: 10.3390/w12102658
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of UV Filters, UV Blockers and Pharmaceuticals in High Rate Algal Ponds Treating Urban Wastewater

Abstract: The present study evaluated the efficiency of a high rate algal pond (HRAP) at pilot scale to remove pharmaceuticals and personal care products (PPCPs) from urban wastewater, including UV-filters and parabens (10), benzotriazoles (4), antibiotics (15), anti-inflammatories (3) and other pharmaceuticals (3). A total of 35 compounds were targeted, of which 21 were detected in the influent wastewater to the HRAP. Removals (RE%) for pharmaceuticals were variable, with efficient eliminations for atenolol (84%) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 77 publications
1
7
0
Order By: Relevance
“…Regarding the high-rate algal pond (HRAP) technique, it can be inferred that the three studies that employed this technique, using a quasi-experimental design, obtained low removal rates for all pharmaceuticals except for ACE (removal between 94.4 and 100%) [ 36 , 45 , 46 ]—results that were consistent with the findings of Vassalle et al (2020) who, in their quasi-experimental study, concluded that HRAP was a natural treatment technique with low cost, which was viable for small populations and presented highly variable removal efficiencies [ 74 ].…”
Section: Resultssupporting
confidence: 69%
“…Regarding the high-rate algal pond (HRAP) technique, it can be inferred that the three studies that employed this technique, using a quasi-experimental design, obtained low removal rates for all pharmaceuticals except for ACE (removal between 94.4 and 100%) [ 36 , 45 , 46 ]—results that were consistent with the findings of Vassalle et al (2020) who, in their quasi-experimental study, concluded that HRAP was a natural treatment technique with low cost, which was viable for small populations and presented highly variable removal efficiencies [ 74 ].…”
Section: Resultssupporting
confidence: 69%
“…The stability of TMP in the abiotic and biotic batches can be explained by the high pK a values of this substance and its low K ow , which would prevent biomass adsorption, favouring the dissolution of this compound in the aqueous phase (Vassalle et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The stability of TMP in the abiotic and biotic batches can be explained by the high pK a values of this substance and its low K ow , which would prevent biomass adsorption, favouring the dissolution of this compound in the aqueous phase (Vassalle et al, 2020).…”
Section: Antibiotics Removalmentioning
confidence: 99%
“…The relationship between CLA concentration in the media and the decrease in pH suggests that this pH drop might be the cause of CLA desorption from the biomass into the media, probably due to the changing of the protonation state of the molecule. Vassalle et al (2020) previously described how the WW pH might contribute to the removal of pharmaceuticals by changing the protonation of their functional groups. The pKa of CLA is 8.99, which indicates that this compound exists in the cation form at pH values of 5 to 9 (McFarland et al, 1997).…”
Section: Biosorptionmentioning
confidence: 99%